Diagnóstico do uso público para o planejamento e gestão na Ilha do Bom Abrigo, Litoral Sul do estado de São Paulo - Spironello, Emanuelle (2023)
Ilha do Bom Abrigo has as a characteristic related to management, the overlapping of institutional spheres, having a growing tourism, however, without planning and regulation. This study sought to describe the profile of visitors and tourism operators, the dynamics of public use, including the evaluation of regulars on the limit of use of the beach strip and the characterization of management performance in the territory. For this, remote questionnaires were applied to two study groups: (a) visitors and (b) nautical operators. The data were interpreted and submitted to multiple correspondence analysis and the description of co-management was based on consultation with the planning and ordering instruments and documentation of the Bom Abrigo Working Group. The profile of visitors with a high level of education, interests and expectations related to landscape and nature, indicated openness to the promotion of environmental education programs. The nautical workers are from Cananéia, self-employed and work in the sports and recreation sector. The context of conservation units existing in the municipality favor the understanding of the sector on the subject and should be the target of educational processes that include training and insertion in spaces of participatory management. The dynamics of public use consists of local tourism, whose beach and boardwalk are the main attractions. The lack of infrastructure and difficult access are obstacles to tourism, however, the prohibition does not reduce anthropic pressures, given the lack of inspection and the discontinuity of political articulation between the responsible bodies. Despite this, the institution of the beach as an area of interest for tourism is an achievement, whose definition and implementation of planning instruments are urgent and necessary. In the evaluation of visitors and operators, the limits of use of the beach strip include 30 to 60 people simultaneously, with 5 to 10 boats concurrently in the vicinity of the island and the average visitation time of 3 to 4 hours. These data can guide carrying capacity studies, which may be revised in the future, after the implementation of sanitation infrastructure, research and monitoring of physical and biological aspects, indicators of environmental quality. Long-term studies, reconciled with face-to-face diagnostic strategies, may also contribute to a better delineation of the profiles and patterns of public use in the territory, including the insertion of other key actors, such as fishermen and users of private vessels. The success of the process of construction and implementation of planning instruments depends on participation and social control, as well as the definition of competences and institutional-administrative attributions for the regulation of tourism.